Anagliptin ameliorates albuminuria and urinary liver-type fatty acid-binding protein excretion in patients with type 2 diabetes with nephropathy in a glucose-lowering-independent manner. Issue 1 (7th July 2017) - Kitada, Munehiro; Tsuda, Shin-ichi; Konishi, Kazunori; Takeda-Watanabe, Ai; Fujii, Mizue; Kanasaki, Keizo; Nishizawa, Makoto; Nakagawa, Atsushi; Koya, Daisuke
Abstract : Objective: The objective of this study is to elucidate the effect of anagliptin on glucose/lipid metabolism and renoprotection in patients with type 2 diabetic nephropathy. Methods: Twenty-five patients with type 2 diabetic nephropathy received anagliptin 200 mg/day for 24 weeks, and 20 patients who were switched to anagliptin from other dipeptidyl peptidase-4 (DPP-4) inhibitors were analyzed regarding primary and secondary endpoints. The primary endpoint was change in hemoglobin A1c (HbA1c) during treatment with anagliptin. Additionally, we evaluated changes in lipid data (low-density lipoprotein-cholesterol, high-density lipoprotein-cholesterol and triglyceride), blood pressure (BP), urinary albumin to creatinine ratio (UACR), liver-type fatty acid-binding protein to creatinine ratio (ULFABP) and renal function (estimated glomerular filtration rate and serum cystatin C) as secondary endpoints. Results: After switching to anagliptin from other DPP-4 inhibitors, the levels of HbA1c in the 20 participants showed no significant change, 7.5%±1.2% at 24 weeks compared with 7.3%±0.9% at baseline. The levels of the log10-transformed UACR were significantly reduced from 1.95±0.51 mg/g creatinine (Cr) at baseline to 1.76±0.53 mg/g Cr at 24 weeks after anagliptin treatment (p<0.01). The percentage change in the UACR (Δ%UACR) from baseline to 24 weeks was also significantly lower by −10.6% (p<0.001). Lipid data, systolic BP and renal function were not changed during anagliptin treatment. Additionally, ULFABP in eight participants, who had ≥5 µg/g Cr at baseline, was significantly decreased from baseline (8.5±2.8 µg/g Cr) to 24 weeks (3.1±1.7 µg/g Cr, p<0.01) after anagliptin treatment, and the percentage change in the ULFABP during anagliptin treatment was −58.1% (p<0.001). Conclusions: Anagliptin induced no significant change in HbA1c, lipid data, systolic BP and renal function. However, anagliptin reduced the UACR and ULFABP, although without a corresponding change in HbA1c, indicating direct action of anagliptin on renoprotection in patients with type 2 diabetic nephropathy.